2015
DOI: 10.1590/0104-07072015003760013
|View full text |Cite
|
Sign up to set email alerts
|

Being cared by a family member: the existential feelings of cancer patients

Abstract: The present article aimed to understand the daily life of cancer patients under palliative care while experiencing home care provided by family members. This was a Heideggerian phenomenological study with 20 patients being treated at the primary health care service of Northeast Paraná, Brazil, between November 2012 and February 2013. Data collection was based on the following research guiding question: What has been your experience of being cared for by your family? Phenomenological analysis was conducted by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
0
11
0
3
Order By: Relevance
“…In the research, a total of 154 studies were found, publications (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) were relevant for this review, since they met the study question and pre-established criteria, as explained in the analysis flowchart ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the research, a total of 154 studies were found, publications (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) were relevant for this review, since they met the study question and pre-established criteria, as explained in the analysis flowchart ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…People consider that their family is close to them at that moment, but at the same time distant. This causes difficulties in the process as their desire is to get greater support from the family, 14 which facilitates adaptation strategies and reduces uncertainty. In this same sense, social support prevents the uncer-tainty.…”
Section: Discussionmentioning
confidence: 99%
“…The spouse, the children and grandchildren are among the main caregivers. [20][21] According to authors, 17 in all societies, women take on the main responsibilities of caring for children, the sick and the elderly, in addition to most of the domestic care. It is characteristic the care provided by the woman-centered family nucleus.…”
Section: Methods Introductionmentioning
confidence: 99%
“…It should be emphasized that the identity of this patient is in this environment, in his personal objects, still allowing, within the capacities of each one, to maintain his relationship with friends and neighbors in order not to lose the bond that already existed. [21][22] In the second category, which encompasses family strategies with a greater emphasis on palliative care, in which one perceives an instrumental scenario with more technical elements of this specificity. There is a multiprofessional team that specializes in this type English/Portuguese J Nurs UFPE online., Recife, 12(7):2039-49, July., 2018 2047 of care, which provides assistance, taking into account all aspects of the human being, and prepares the family to play its role both in the hospital and in the home.…”
Section: Methods Introductionmentioning
confidence: 99%